Analisis Minat Membaca Siswa di Madrasah Aliyah Program Khusus Al-Azhar Sempu Banyuwangi - Moh. Iqbal Robbal Idam; Robisha Zarifa Ribaah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study was conducted at MA PK Al-Azhar Sempu, Banyuwangi Regency. The purpose of this study was to determine students' interest in reading, their enjoyment of reading during classroom learning, and their enjoyment of reading fiction and scientific books. The research method used in this study was descriptive, and the type of research used was qualitative. The population in this study consisted of 86 students from grades X, XI, and XII. The sample used in this study consisted of 32 students, and the researcher employed two techniques: interviews and questionnaires. Based on the results of this study, it shows that students' reading interest is moderate or sufficient. Still, there is an opportunity for students to increase their reading interest by reading books that are easy to digest, such as novels, as well as the availability of additional facilities provided by the Madrasah, with additional support from teachers to motivate students to continue enjoying reading.